Berat Basah dan Kadar Vitamin C pada Nata De Soya Limbah Cair Tahu dengan Pemanis Gula Batu - Wati, Desti Ambar; Ika Azahra, Rismantia; Junita, Dera Elva (Journal Aisyah University, 2024)
Nata is a food product fermented by Acetobacter xylinum which has a white to light gray color, a sour aroma, a bland or slightly sweet taste, slightly transparent, and a chewy texture. Tofu liquid waste still contains nutrients such as 2 g carbohydrates, 1.75 g protein, 1.25 g fat, 0.001 g crude fiber and 4.5 mg calcium which have the potential to be developed into food products that are beneficial for health. This research aims to determine the characteristics of nata de soya with the addition of rock sugar which is assessed based on wet weight and vitamin C content. Fermentation was carried out for 14 days in the Culinary and Dietetics Laboratory of the Nutrition Study Program, Aisyah Pringsewu University. Vitamin C levels were analyzed at the Lampung State Polytechnic Agricultural Products Technology Laboratory (POLINELA). The research results revealed that nata de soya with the addition of 42 g of rock sugar produced a wet weight of 317 g and a vitamin C content of 0.36 mg/g.